The evolution of the negotiating role of the state in a field the salaries - BELOULMI, Amani (Journal of Human Sciences, 2020)
Although the state determines the salaries of its employees with mandatory legal and regulatory provisions, it has progressively lost its ability to act individually in this area. This option is either optional for the comparison between civil service salaries an other sectors wages in order to achieve the justice necessary to maintain social security, which is done only through collective bargaining based on the participation of the public sector. All active parts, or is to public officials who use their collective rights, namely the right of association and the right to strike, which were formed for them and remain the most effective way to achieve the goals benefits.